2016
DOI: 10.2174/1570161114666160229115553
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HMG-CoA Reductase Inhibition on Vascular Smooth Muscle Cells Extracellular Matrix Production: Role of RhoA

Abstract: Cholesterol-lowering effects apart, statins can improve the endothelial function, stabilize the atherosclerotic plaques, decrease the oxidative stress and inflammation and inhibit the thrombogenic response by means of the inhibition of isoprenoids, which serve as lipid attachments for intracellular signaling molecules. We aimed to evaluate whether the effect of statins on RhoA activity mediate extracellular matrix production, particularly affecting collagen type I, in smooth muscle cells (SMCs). Our results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Lovastatin is an inhibitor of HMG-CoA reductase in the process of cholesterol synthesis. It can effectively suppress cholesterol synthesis and is therefore applied to hypercholesterolemia treatment in the clinic ( 13 , 14 ). Besides its lipid-lowering function, there is evidence to suggest that lovastatin can inhibit tumor cell proliferation, angiogenesis, invasion, and metastasis, and can induce apoptosis ( 15 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lovastatin is an inhibitor of HMG-CoA reductase in the process of cholesterol synthesis. It can effectively suppress cholesterol synthesis and is therefore applied to hypercholesterolemia treatment in the clinic ( 13 , 14 ). Besides its lipid-lowering function, there is evidence to suggest that lovastatin can inhibit tumor cell proliferation, angiogenesis, invasion, and metastasis, and can induce apoptosis ( 15 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, along with their cholesterol-lowering effects, numerous investigations have demonstrated that statins have immunomodulatory activities via mevalonate-independent and -dependent mechanisms (Sarrabayrouse et al, 2017). They suppress the activity of GTPases belonging to the Ras and Rho families, which govern a variety of cellular activities, including cell death, metastasis, and immunological responses (Palomino-Morales et al, 2016). Statins also affect the immune system by inhibiting the generation of pro-inflammatory cytokines and activating CD8+ T cells (Côté-Daigneault et al, 2016).…”
Section: Role Of Immunosensitizing Drugs In Cancer Diseasesmentioning
confidence: 99%